2015
DOI: 10.1177/0894318415614902
|View full text |Cite
|
Sign up to set email alerts
|

On Being a Father or Sibling in Light of the Humanbecoming Family Model

Abstract: The following article provides an updated discussion on two Parse grounded exploratory descriptive studies in light to her recently added humanbecoming family model. The comments of the fathers and siblings from the studies reveal that family life is unpredictable and that family relationships are paradoxical evolutional emergences of shifting hopes and dreams. The humanbecoming family model provided a useful way to consider fathering and being a sibling, as unexpected unfoldings of joy-sorrow reveal purposefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Subcategories of this category included appreciation of the little things , transformation of expectations , living in the moment and maintaining a positive attitude . Recent studies have reported a transformation of fathers' expectations of their lives and their children with disabilities (Baumann and Braddick ; Shave and Lashewicz ), which agrees with the majority of the fathers in this study. Moreover, the ‘pace of life’ found in this study is similar to the day‐to‐day life of families with a member with a disability as reported by Schippers and Van Hoheemen ().…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…Subcategories of this category included appreciation of the little things , transformation of expectations , living in the moment and maintaining a positive attitude . Recent studies have reported a transformation of fathers' expectations of their lives and their children with disabilities (Baumann and Braddick ; Shave and Lashewicz ), which agrees with the majority of the fathers in this study. Moreover, the ‘pace of life’ found in this study is similar to the day‐to‐day life of families with a member with a disability as reported by Schippers and Van Hoheemen ().…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…A sense of a different identity for families was discussed by Baumann and Braddick (2016) in considering two humanbecoming descriptive exploratory studies that reviewed 23 stories of being a father or sibling of children who are born significantly different from other families and had unfamiliar needs. Fathering was described by the participants as unlike other projects in their lives in that fathering was unpredictable and not in their control.…”
Section: Family Storytelling As a Mode Of Personal And Family Becomingmentioning
confidence: 99%
“…The paper is based on two interviews, using questions similar to those used by one of the authors (S.L.B.) with his study of fathers and sibling (Baumann & Braddick, 2016). Following the interviews is a discussion on the loss of a child, with a few comments on the immigration of nurses.…”
mentioning
confidence: 99%